2012
DOI: 10.3389/fonc.2012.00076
|View full text |Cite
|
Sign up to set email alerts
|

Three to Tango: MUC1 as a Ligand for Both E-Selectin and ICAM-1 in the Breast Cancer Metastatic Cascade

Abstract: Cancer cell tethering and rolling on the vascular wall is facilitated by various selectin: glycoprotein interactions which lead to eventual extravasation and metastases. The aberrantly underglycosylated mucin MUC1 has been shown to both abundantly express selectin binding moieties (sialyl Lewis x and a) and to consistently expose its core epitope. Flow cytometry was used to determine MUC1 expression on ZR-75-1 and MCF7 cells, while immunofluorescence microscopy was used to confirm the aberrant form of MUC1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
40
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 31 publications
6
40
0
Order By: Relevance
“…Geng et al [44] demonstrated that efficient binding is possible between ICAM-1 and MUC1 whose expression increases with the invasivity of breast cancer cells [31]. Our measurements using flow cytometry demonstrated clearly that T24 cells express only MUC1 whereas J82 cells express MUC1 and CD43 (Figure 9).…”
Section: Discussionsupporting
confidence: 50%
“…Geng et al [44] demonstrated that efficient binding is possible between ICAM-1 and MUC1 whose expression increases with the invasivity of breast cancer cells [31]. Our measurements using flow cytometry demonstrated clearly that T24 cells express only MUC1 whereas J82 cells express MUC1 and CD43 (Figure 9).…”
Section: Discussionsupporting
confidence: 50%
“…Collectively, these results would suggest that the most plausible molecules dictating the firm adhesion of the MDA-MB-231 cells to the inflamed HUVECs are MUC-1 and ICAM-1; and the cellular expression of both molecules can be efficiently modulated by curcumin. However, this would not exclude the possible involvement of other inflammatory molecules, such as E-selectin, which have been shown to interact with MUC-1 and whose cell membrane expression is known to be down regulated by curcumin (24, 46). …”
Section: Resultsmentioning
confidence: 99%
“…The combined observations of a coactivator function for SSA in ER-mediated transcription, the presence of SSA on the MYC promoter, and SSA-mediated promotion of colony formation in MCF7 cells suggest that ER and SSA induce tumorigenicity by increasing the transcriptional expression of MYC. Furthermore, ZR75 cells expressing more SSA with lower CoAA shows higher metastatic potential than MCF7 cells expressing less SSA with higher CoAA (30). A recent report hinted that SSA potentially contributes to tumorigenesis of lung cancer possibly through the interaction with TRIB2 to downregulate CEBP/␣ (31).…”
Section: Discussionmentioning
confidence: 99%